Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 11 - Additional Topics - 11.4 - Complex Numbers - Concept Quiz 11.4 - Page 493: 10



Work Step by Step

To multiply complex numbers, we multiply each term of the first number by each term of the second number and then simplify. $(-2-i)(-3+2i)$ $=(-2)(-3)+(-3)(-i)+(-2)(2i)+(-i)(2i)$ $=6+3i-4i-2i^2$ $=6-i-2i^2$ Since $i^2=-1$, we obtain: $6-i-2(-1)=6-i+2=8-i$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.